Alimentación de pavos americanos big-6 con una dieta balanceada más la suplementación de nabo (brassica rapa l.) en la fase de engorde. - Suárez Suárez, Gabriela Natalia (2016)
The present research is led to out in them properties of the Finca Experimental "La Maria", belonging to the University Technical State of Quevedo (UTEQ), located in the km 7 ½ Via Quevedo-El Empalme, in Mocache city. An experimental trial was conducted to know the productive performance of turkeys American BIG-6 (food consumption: CA; weight gain: GP; feed conversion: lime and carcass performance: RC), fed with a balanced diet and supplemented with turnip (Brassica rapa L.), moreover the organoleptic characteristics and profitability. The treatments evaluated were: T1 (witness). T2 (balanced + 10.0% of turnip) and T3 (balanced + 15.0% of turnip). It applied a design fully to the random (DCA) with five repetitions. The experimental unit was formed by four turkeys. To determine the differences between middle is applied the test of Tukey (P≤0. 05) and for the analysis economic the relationship benefit cost. The statistical package SAS Version 9.0 was used for data analysis. The greatest (P≤0.05) CA, GP, lime and higher profitability T3 treatment recorded it (160.75 g animal-1 day-1; 78.51 g animal-1 day-1, 2.0-87.87%, respectively). Also showed the best organoleptic characteristics (texture, flavour, aroma and juiciness).